Формування команди гравців на основі аналізу їх переваг у попередніх іграх - Біляєв, М. П. (ХНУРЕ, 2019)
This thesis is devoted to the formation of a team of players, based on the analysis of their previous games and the identification of the best roles for them in the game Dota 2. The problem is that most players often cannot objectively assess the role they can play best, and the lack of role-playing roles. Because of this, at the stage of selecting characters, it is difficult for players to agree on who will play the role. This results in wrong choices of characters and unnecessary number of players in the same role. The task is to determine in which role the player shows himself the best and to form a team in which there will be no ambiguity among the team members regarding their role in the match.